2010
DOI: 10.1111/j.1524-4733.2009.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Impacting Health State Index Scores, Measured by the EQ-5D of Females with Stress Urinary Incontinence Symptoms

Abstract: This article describes the characteristics of patients at the SUIT enrollment visit, and demonstrates that the number of incontinence episodes has a significant impact on the EQ-5D index score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
1
25
2
Order By: Relevance
“…In this study, type of UI did not predict QoL although it has been suggested that there is a relationship between the type of UI and QoL (Dugan et al, 1998;Senra and Pereira, 2014;Tincello et al, 2010;Yu et al, 2003). In fact, the level of severity of the UI seems to impact more the patient's QoL than the type of UI, as Barentsen et al (2012) have found.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, type of UI did not predict QoL although it has been suggested that there is a relationship between the type of UI and QoL (Dugan et al, 1998;Senra and Pereira, 2014;Tincello et al, 2010;Yu et al, 2003). In fact, the level of severity of the UI seems to impact more the patient's QoL than the type of UI, as Barentsen et al (2012) have found.…”
Section: Discussioncontrasting
confidence: 56%
“…Two studies defined groups by the frequency of incontinence episodes [7,19]. In one study, three groups were defined and the mean EQ-5D consistently reflected differences between groups and the differences were statistically significant [19].…”
Section: Resultsmentioning
confidence: 99%
“…In one study, three groups were defined and the mean EQ-5D consistently reflected differences between groups and the differences were statistically significant [19]. In the second study, five groups were defined [7].…”
Section: Resultsmentioning
confidence: 99%
“…Because this is a secondary analysis, our data were limited to that originally collected for the primary study. Therefore, the results of our regression analyses are less stable than they would otherwise be with a larger sample size and we were unable to control for confounding factors, such as socioeconomic status and depression, that could impact the prevalence of SUI [20,21]. Some urodynamic parameters, such as leak point pressure, may demonstrate greater variation based on user technique, and therefore may be subject to a larger margin of error.…”
Section: Discussionmentioning
confidence: 97%